WEBSITE GOOGLE SITES SEBAGAI PERANGKAT PEMBELAJARAN BAGI GURU - Subnarulloh, Subnarulloh; Sugiharti, Rini Endah; Rikmasari, Rima (An-Nizam, 2024)
The aim of training and counseling on making learning tools is to use the Google website as a teaching tool. Elementary school teachers in Bojongmangu sub-district, in collaboration with teachers implementing the independent curriculum, provide devices innovative and creative learning. This training is qualitative research with observations, discussions and seminars, This seminar activity aims to increase insight into how to create Google sites for elementary school teachers in Sukabungah village, Bojongmangu district. Based on research conducted by elementary school teachers in Bojongmangu sub-district, teachers' ability to create lesson plans for the Mardeka curriculum is still limited, resulting in an unsatisfactory learning process. Teachers also do not have the ability to create interesting, innovative and creative learning materials. Teachers use media that is appropriate for students. Teachers should not overcrowd classes, and in some cases, learning material is limited to a certain number of books. In addition, teachers do not use technology in their teaching process; instead, all teaching methods are done by hand, which results in teachers' knowledge being inadequate to meet the demands of the curriculum. This research will produce products that can be used by teachers in the classroom, such as Google Sites. Due to the availability of Google sites, teachers can focus on developing their important skills, which are necessary for their field of work in education. The results of this research can be used as a guide for other teachers in other schools to increase the use of Google Sites for learning.